(untitled) (AYUSHDHARA, 2024)
Bhasha or language is the most important media of communication for the human race since ages, Various languages as per their specific region adapts a unique style of grammaticalization. Sanskrit, known as the language of Gods is the oldest language with the most scientific grammaticalization. Ayurveda, the science of life has been narrated and pass down since ages by virtue of Sanskrit. The Ayurvedic Tantras are composed in Sanskrit Shlokas, these verse are studied and analysed for acquiring the proper knowledge of Ayurveda. Without the Sanskrit language, it is unthinkable of obtaining the knowledge of Ayurvedic healing. The newfangled ventures in the field of literature has re-highlighted the old languages and their learning techniques, Sanskrit is studied in many educational institute for its scientific ethnicity and diversity. Similarly, Sanskrit in Ayurvedic literature needs to be upgraded and highlighted efficiently. Profuse concepts applied in the system of Ayurveda, are kindred with Sanskrit literature. These, concept when studied culminated in highlighting the importance of Sanskrit Sahitya in Ayurveda.